Motivasi, Persepsi, dan Perilaku Pasca Konsumsi Wisatawan Domestik Terhadap Kuliner Sate Klatak di Imogiri Timur Yogyakarta - Dewi, Juwita Sari Rizky Millenia; Fonsen, Muhammad Jhony; Aprilia, Annisa Dwi; Syahri , Aqila Ramiza; H, Shafandra Cahya L; Zuhair , Yasin Adib; Wachyuni, Suci Sandi (Sasdaya: Gadjah Mada Journal of Humanities, 2022)
Klatak satay is an iconic food originating from the Bantul Regency of Yogyakarta. Sate klatak was named the Intangible Cultural Heritage of Indonesia in 2019 by the Ministry of Education and Culture. As an Intangible Cultural Heritage, satay klatak needs to be preserved so that the regeneration process continues and its existence remains sustainable. Tourists coming to eat Sate Klatak have various motivations. The purpose of this study is to review the motivation, perception, post-consumption behaviour of domestic tourists Sate Klatak East Imogiri, Yogyakarta. This research uses a quantitative approach with a survey method. The data collection technique is by distributing online questionnaires via WhatsApp and Instagram. The results showed that the biggest motivation for tourists to consume satay klatak Imogiri was recommendations from friends and relatives. Furthermore, Sate Klatak East Imogiri is incredibly well-received because of its popularity, taste, and appearance. Tourists also show satisfaction in post-consumption behavior, namely, returning and recommending it to relatives. The theoretical implication of this study is that these three variables can be used as indicators of local culinary evaluation. Meanwhile, as a practical implication, the research results can be used as suggestions for local culinary development in destinations, especially Sate Klatak East Imogiri